KUIS SEBAGAI MEDIA PEWARTAAN KITAB SUCI BAGI KAUM MUDA KATOLIK - Agustinus Wisnu Dewantara (Bahasa Indonesia, 2019)
Theological inquiry and Holy Bible preaching are not the activities of reading. It would be a human area that Bible must explored more and more. Especially for the adolescent, the preaching of Bible must serve the dynamization of them. In this context, knowing that study and preaching The Holy Bible are the problems of methodology. Quiz is the one among many methods of teaching the Holy Bible to the young peoples. Those people arefamiliar, fun, andfull ofknowledge. Thispaper will punctuate the option for us to apply quiz in adolescental catechesis. Church must be helped in according to preach the value offaith for young people. Teaching with quiz may be one of the effective evangelization methodsfor the young peoples.